Perovskite battery anti-reflection polymer film with lead ion sealing function, preparation and application of perovskite battery anti-reflection polymer film

The pyramid structure antireflective polymer film prepared by modifying polyvinyl alcohol solves the problems of lead ion leakage and light energy loss in perovskite solar cells, and achieves the effect of efficient storage of lead ions and improving photoelectric conversion efficiency.

CN119286011AActive Publication Date: 2025-01-10BEIJING INST OF TECH

Patent Information

Application Number
CN202411394353.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-10
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

Perovskite solar cells are prone to leakage of lead ions due to external shock during use, and Fresnel reflection leads to loss of light energy, affecting battery performance and environmental safety.

Method used

By modifying polyvinyl alcohol with a pyramid structure, antireflective polymer films are prepared for the light-receiving surface of perovskite solar cells to reduce lead ion leakage and light energy by modifying the polyvinyl alcohol by using the pyramid structure. loss.

Benefits of technology

This film can quickly and efficiently store lead ions, reduce lead ions leakage concentration, improve photoelectric conversion efficiency, and enhance battery safety and performance stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286011A_ABST
    Figure CN119286011A_ABST
Patent Text Reader

Abstract

The invention relates to an antireflection polymer film with a lead ion sealing function for a perovskite cell, and preparation and application thereof, and belongs to the technical field of perovskite solar cells. PVA and water are mixed and heated to be dissolved, and a transparent and clear PVA solution is obtained; the preparation method comprises the following steps: sequentially adding a phosphoric acid solution, dibasic phosphate and a transparent plasticizer into a PVA (Polyvinyl Alcohol) solution under continuous heating, respectively reacting for more than 1 hour, pouring the obtained modified polymer solution on a substrate with a micro-nano structure, and naturally curing and stripping to obtain the antireflection polymer film PFPF with lead ion sequestration. When the PFPF is applied to the light receiving surface of the perovskite solar cell, Pb < 2 + > leaked by the PSCs when the light receiving surface is damaged can be reduced, and Fresnel reflection of the light receiving surface can be reduced, so that the light energy loss is reduced, and the photoelectric conversion efficiency of the PSCs is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an anti-reflection polymer film for a perovskite cell with a lead ion sealing function, preparation and application thereof, and in particular to a functionalized anti-reflection film for reducing lead ions leaking into water from a perovskite solar cell, belonging to the technical field of perovskite solar cells. Background Art

[0002] Perovskite solar cells (PSCs) have attracted much attention due to their high absorption coefficient, low manufacturing cost and low-temperature solution processing. After more than a decade of rapid development, the certified power conversion efficiency (PCE) of PSCs has reached 26.21%, becoming a rising star comparable to commercial silicon solar cells. However, the toxic lead (Pb) in PSCs 2+ ) has the risk of leakage into the environment and is one of the serious obstacles in the commercialization of PSCs. The current research results show that Pb 2+ The use of Pb cannot be completely replaced, so it is necessary to develop effective 2+ The front side (light-receiving side) of PSCs faces upward when in use. On the one hand, the light-receiving side of PSCs is more susceptible to external impact (such as hail, flying stones, etc.) than the back side (metal electrode side) and is damaged, causing Pb 2+ The risk of leakage is greater. On the other hand, due to the large difference in refractive index between the light-receiving surface of PSCs and air, Fresnel reflection will occur, causing light energy loss and ultimately leading to a decrease in the PCE of PSCs.

[0003] A series of Pb 2+ Containment strategies include physical encapsulation barriers outside the device and chemical Pb 2+ Sequestration materials to mitigate Pb 2+ The external physical packaging barrier reduces the chance of device damage and reduces Pb 2+ Risk of leakage. Using Pb in the perovskite layer or on the surface of the perovskite layer 2+ Sealing materials can not only be used in Pb 2+ When leakage occurs, 2+ The charge transport layer (CTL) is a key component of PSCs. 2+ New CTL with sealing function or Pb 2+ Doping of sealing materials in common CTL can not only effectively reduce Pb 2+ The leakage of PSCs can also be improved by developing new Pb 2+ Sealing material as encapsulation layer or doping Pb in the encapsulation layer2+ Sealing materials can also effectively reduce Pb 2+ Give way.

[0004] However, once the physical packaging barrier fails under extreme impact, it cannot prevent Pb 2+ Leakage. Pb used inside or on the surface of the perovskite layer 2+ In order not to affect the performance of PSCs, the amount of sealing materials used is usually small, so Pb 2+ The storage capacity is limited, and whether it has Pb 2+ New CTL with storage capacity may be used to store Pb 2+ The sealing material is combined with the traditional CTL. The thinner CTL cannot transfer the Pb in the perovskite layer hundreds of nanometers thick. 2+ Completely sealed. Despite the use of Pb 2+ Sealing materials as encapsulation layers can effectively reduce Pb 2+ However, they have non-negligible absorption characteristics in the visible light wavelength range and are therefore mainly used on the back side of the device. Therefore, when only the light side of the device is damaged, it is necessary to prevent Pb 2+ The effect of leakage will be reduced or even completely ineffective. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide an anti-reflective polymer film for perovskite cells with lead ion sealing function, preparation and application thereof, which can be used to reduce the lead leakage hazard and light energy loss of perovskite solar cells. Applying PFPF to the light-receiving surface of perovskite solar cells can reduce the Pb leakage of PSCs when the light-receiving surface is damaged. 2+ , and can also reduce Fresnel reflection on the light-receiving surface, thereby reducing light energy loss and improving the photoelectric conversion efficiency of PSCs. 3 PO 4 ), dihydrogen phosphate and transparent plasticizer to modify polyvinyl alcohol (PVA), and then use the casting method to prepare the modified PVA into a film with a pyramid structure on the surface. The preparation method of PFPF is simple, and it not only has the advantages of fast sealing speed and high sealing capacity, but also can effectively reduce light energy loss, and can be applied to the light-receiving surface of PSCs.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows.

[0007] A method for preparing an anti-reflection polymer film for a perovskite battery with a lead ion sealing function, the method steps comprising:

[0008] Mix polyvinyl alcohol (PVA) and water, heat and dissolve to obtain a transparent and clear PVA solution; add a phosphoric acid solution to the PVA solution under continuous heating, stir for more than 1 hour, then add a dihydrogen phosphate solution, stir for more than 1 hour, and finally add a transparent plasticizer, stir for more than 1 hour to obtain a modified polymer solution;

[0009] The modified polymer solution is poured onto a substrate having a micro-nano structure, cured naturally, and peeled off to obtain an anti-reflection polymer film having lead ion sealing;

[0010] Wherein, the molar ratio of the PVA, phosphoric acid, dihydrogen phosphate and transparent plasticizer is 100:0.5-1:2-4:50-70.

[0011] Preferably, the viscosity of the PVA solution is 50-70 mPa.s. More preferably, the viscosity of the PVA solution is 54-66 mPa.s; and the alcoholysis degree of the PVA solution is 98 mol%-99 mol%.

[0012] Preferably, the disalt of hydrogen phosphate is one or more of dipotassium hydrogen phosphate, dicalcium hydrogen phosphate and diammonium hydrogen phosphate.

[0013] Preferably, the transparent plasticizer is glycerol.

[0014] Preferably, the absorption wavelength of the lead-based perovskite solar cells (lead-based PSCs) is less than the size of the micro-nano structure ≤ 10 microns.

[0015] Preferably, the micro-nano structure is a pyramid structure.

[0016] An anti-reflection polymer film for perovskite cells with lead ion sealing function is prepared by the above method.

[0017] Preferably, the polymer film has a thickness of 150 to 200 microns.

[0018] An application of the anti-reflective polymer film for perovskite cells with lead ion sealing function described in the present invention is to attach the film to the light-receiving surface of the lead-based perovskite solar cell.

[0019] Beneficial Effects

[0020] The present invention uses phosphoric acid, dihydrogen phosphate and a transparent plasticizer to modify PVA to obtain a micro-nanostructured anti-reflection polymer film PFPF. PFPF can react with Pb 2+ Rapid formation of extremely low-solubility lead-hydroxyapatite (Pb 5 (PO 4 ) 3 (OH)) to reduce Pb 2+, and the hydroxyl groups of PVA can react with Pb 2+ Complexation further reduces Pb in solution 2 + The results of adsorption isotherms and adsorption kinetics tests show that PFPF can store Pb 2+ The speed is extremely fast, and most of the Pb can be sealed within 10 seconds. 2+ , and has a high 2 The storage capacity of Pb in typical PSCs 2+ The micro-nano structure on the surface of PFPF can convert reflected light into incident light and re-enter PSCs to reduce light energy loss. In addition, the micro-nano structure can scatter the incident light and increase its optical path in PSCs, thereby increasing the absorption of light by PSCs.

[0021] After applying PFPF to the light-receiving surface of lead-based PSCs, PFPF significantly reduced the Pb content of PSCs in various harsh drip and immersion tests. 2+ Leakage, Pb leaked from PSCs can always be 2+ The concentration is reduced to below the sewage discharge standard, which greatly improves the safety of PSCs. PFPF can effectively reduce the reflection of the PSC surface and increase its absorption of incident light, thereby enhancing the PCE by more than 7%. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the infrared spectrum of PFPF in Example 1.

[0023] Figure 2 is the Pb leaked from PSCs by PFPF in Example 1 2+ The storage rate.

[0024] Figure 3 This is the test result of PFPF on the reflectivity of PSCs in Example 1. DETAILED DESCRIPTION

[0025] The present invention will be further described in detail below in conjunction with specific embodiments.

[0026] In the following examples, the Pb in aqueous solution was measured using an inductively coupled plasma emission spectrometer and an inductively coupled plasma mass spectrometer. 2+ The storage efficiency of Pb leaked into the aqueous solution from PSCs without PFPF was determined. 2+ Concentration and Pb leakage into aqueous solution from PSCs using PFPF 2+ The difference in concentration between the Pb leaked into the aqueous solution from PSCs without PFPF 2+ The concentration ratios were calculated as percentages.

[0027] The rigid PSCs structure is:

[0028] Glass / ITO / SnO 2 / Cs 0.15 (FA 0.97 MA 0.03 ) 0.85 Pb(I 0.97 Br 0.03 ) 3 / Spiro-OMeTAD / MoO 3 / Ag.

[0029] The structure of flexible PSCs is: PEN / ITO / 2PACz / (Cs 0.15 FA 0.85 )Pb(I 0.95 Br 0.05 ) 3 / C 60 / BCP / Ag.

[0030] The structure of PSCs using PFPF is as follows: PFPF with a thickness of 160 microns is attached to the light-receiving surface of PSCs.

[0031] Embodiment 1:

[0032] 0.5 g of PVA powder was added to 20 mL of deionized water, and then heated in an oil bath at 90 °C for 2 hours until it was completely dissolved to obtain a transparent and clear PVA solution. Then 200 μL of H 3 PO 4 Solution (PVA / H 3 PO 4 ), continue stirring and heating for 1 hour. Then add 1 mL of K 2 HPO 4 solution (PVA / PB) and continue stirring and heating for 1 hour. Finally, 0.5 mL C 3 H 8 O 3 , and heated with stirring for 1 hour. Pour the above solution onto an inverted pyramid (length, width and height are all less than 10 microns) silicon wafer, wait for it to solidify and peel off to obtain PFPF. Figure 1 As shown, infrared detection proves that the components in PFPF are connected by hydrogen bonds. The structural formula is as follows:

[0033]

[0034] The traditional glass to glass encapsulation method was used to encapsulate PSCs (size 2cm×2cm) with and without PFPF. The specific process is to buckle the metal electrode side of the PSCs with a glass cover plate of the same area and thickness of 1mm, and then apply an appropriate amount of UV curing glue on the edges to ensure that the gap between the PSCs and the glass cover plate can be completely sealed, and then use UV light to irradiate the UV curing glue to cure it. The encapsulated PSCs were impacted with a metal iron ball (diameter 45mm, weight 360g) to simulate external force impacts such as hail impact and flying stone impact.

[0035] The damaged PSCs were placed in a funnel and kept at an angle of about 30° to the table. Then a microinjection pump was used to drip a deionized water solution at the damaged location at an injection rate of 5 mL / h for 3 hours. The dripping solution was collected by a centrifuge tube at the bottom. The solution in the centrifuge tube was collected to test the leaked Pb 2+ Concentration. Figure 2 As shown, the leakage concentrations of the rigid PSC without and with PFPF are 9.32 and 0.0144 ppm, respectively, and the sealing efficiency of the rigid PSC with PFPF exceeds 99.8%.

[0036] The broken PSCs were placed in a beaker, and 36 mL of deionized water was added to completely immerse them at room temperature. The Pb leaked from the solution was measured at different times. 2+ The average leakage concentrations of PSCs without and with PFPF were 12.39 and 0.0101 ppm, respectively, and the sealing efficiency of rigid PSCs with PFPF exceeded 99.9%.

[0037] The damaged PSCs were placed in a funnel and kept at an angle of about 30° to the table. A pH = 4.2 aqueous solution was then dripped onto the damaged location using a microinjection pump at a rate of 5 mL / h for 3 hours. The dripping solution was collected from a centrifuge tube at the bottom. The solution in the centrifuge tube was collected to test the leaked Pb 2+ The leakage concentrations of PSCs without and with PFPF were 19.15 and 0.0149 ppm, respectively, and the sealing efficiency of rigid PSCs with PFPF exceeded 99.9%.

[0038] The damaged PSCs were placed in a beaker, and 36 mL of pH 4.2 aqueous solution was added to completely immerse them at room temperature. The solution was stirred at 500 rpm using a magnetic stirrer for 3 hours, and the Pb leaked from the solution was measured at different times. 2+The leakage concentrations of PSC without and with PFPF were 17.64 and 0.0392 ppm, respectively, and the sealing efficiency of rigid PSC with PFPF exceeded 99.7%.

[0039] Place the damaged PSCs into the funnel and keep it at an angle of about 30° to the tabletop. Then use a microinjection pump to pump pH = 4.2 and Ca 2+ and Mg 2+ A 10 ppm aqueous solution was dripped onto the damaged part at a rate of 5 mL / h for 3 hours. The dripping solution was collected by a centrifuge tube at the bottom. The solution in the centrifuge tube was collected to test the leaked Pb 2+ The leakage concentrations of PSCs without and with PFPF were 12.42 and 0.0420 ppm, respectively, and the sealing efficiency of rigid PSCs with PFPF exceeded 99.6%.

[0040] The damaged PSCs were placed in a beaker and 36 mL of pH 4.2 and Ca 2+ and Mg 2+ The solution was completely immersed in a 10 ppm aqueous solution and stirred at 500 rpm for 3 hours using a magnetic stirrer. The Pb leaked from the solution was measured at different times. 2+ The leakage concentrations of PSC without and with PFPF were 16.09 and 0.261 ppm, respectively, and the sealing efficiency of rigid PSC with PFPF exceeded 98.3%.

[0041] like Figure 3 As shown, the reflectivity of PSC was tested before and after using PFPF using UV-visible-near infrared absorption spectrometer. The results showed that the average reflectivity of PSC in the range of 300-800nm ​​decreased from 10.5% to 5.7%.

[0042] The current density-voltage (JV) curves of five rigid and flexible PSCs before and after using PFPF were tested. The average short-circuit current and photoelectric conversion efficiency of rigid PSCs increased from 24.02 mA / cm 2 and 22.77 to 25.58 mA / cm 2 and 24.38%, the short-circuit current and photoelectric conversion efficiency of flexible PSCs increased from 22.71 mA / cm 2 and 20.54% to 24.26 mA / cm 2 and 22.20%.

[0043] Embodiment 2:

[0044] 0.5 g of PVA powder was added to 20 mL of deionized water, and then heated in an oil bath at 90 °C for 2 hours until it was completely dissolved to obtain a transparent and clear PVA solution. Then 200 μL of H 3 PO 4 The solution was stirred and heated for 1 hour. Then 1 mL of Ca 2 HPO 4 The solution was stirred and heated for 1 hour. Finally, 0.5 mL of C 3 H 8 O 3 , and stirred and heated for 1 hour. The above solution was poured onto an inverted pyramid silicon wafer, and then solidified and peeled off to obtain PFPF. The performance of PFPF was similar to that of Example 1.

[0045] Embodiment 3:

[0046] 0.5 g of PVA powder was added to 20 mL of deionized water, and then heated in an oil bath at 90 °C for 2 hours until it was completely dissolved to obtain a transparent and clear PVA solution. Then 200 μL of H 3 PO 4 The solution was stirred and heated for 1 hour. Then 1 mL (NH 4 ) 2 HPO 4 The solution was stirred and heated for 1 hour. Finally, 0.5 mL of C 3 H 8 O 3 , and stirred and heated for 1 hour. The above solution was poured onto an inverted pyramid silicon wafer, and then solidified and peeled off to obtain PFPF. The performance of PFPF was similar to that of Example 1.

[0047] Embodiment 4:

[0048] 0.5 g of PVA powder was added to 20 mL of deionized water, and then heated in an oil bath at 90 °C for 2 hours until it was completely dissolved to obtain a transparent and clear PVA solution. Then 200 μL of H 3 PO 4 The solution was stirred and heated for 1 hour. Then 0.5 mL of K 2 HPO 4 The solution was stirred and heated for 1 hour. Finally, 5 mL of C 3 H 8 O 3, and stirred and heated for 1 hour. Pour the above solution on the inverted pyramid silicon wafer, wait for it to solidify and peel it off to obtain PFPF. The film is immersed in a volume of 9 ml per square centimeter of film with a concentration of about 20 ppm of Pb 2+ More than 85% of Pb can be removed in the solution for three hours 2+ .

[0049] Embodiment 14:

[0050] 0.5 g of PVA powder was added to 20 mL of deionized water, and then heated in an oil bath at 90 °C for 2 hours until it was completely dissolved to obtain a transparent and clear PVA solution. Then 200 μL of H 3 PO 4 The solution was stirred and heated for 1 hour. Then 5 mL of K 2 HPO 4 The solution was stirred and heated for 1 hour. Finally, 0.5 mL of C 3 H 8 O 3 , and stirred and heated for 1 hour. Pour the above solution on the inverted pyramid silicon wafer, wait for it to solidify and peel it off to obtain PFPF. The film is immersed in a volume of 9 ml per square centimeter of film with a concentration of about 20 ppm of Pb 2+ After three hours in the solution, more than 99% of lead ions can be removed.

[0051] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.

Claims

1. A method for preparing an anti-reflective polymer film for a perovskite cell having a lead ion sealing function, characterized in that: The method steps include: PVA is mixed with water and heated to dissolve to obtain a transparent and clear PVA solution; under continuous heating, a phosphoric acid solution is added to the PVA solution and stirred for more than 1 hour, then a dihydrogen phosphate solution is added and stirred for more than 1 hour, and finally a transparent plasticizer is added and stirred for more than 1 hour to obtain a modified polymer solution; The modified polymer solution is poured onto a substrate having a micro-nano structure, cured naturally, and peeled off to obtain an anti-reflection polymer film having lead ion sealing; Wherein, the molar ratio of the PVA, phosphoric acid, dihydrogen phosphate and transparent plasticizer is 100:0.5-1:20-40:50-70.

2. The method for preparing an anti-reflection polymer film for a perovskite cell having a lead ion sealing function according to claim 1, characterized in that: The viscosity of the PVA solution is 50-70 mPa.s.

3. The method for preparing an anti-reflective polymer film for a perovskite cell having a lead ion sealing function according to claim 1, characterized in that: It is 98mol%~99mol%.

4. The method for preparing an anti-reflective polymer film for a perovskite cell having a lead ion sealing function according to claim 1, characterized in that: The dihydrogen phosphate salt is one or more of dipotassium hydrogen phosphate, dicalcium hydrogen phosphate and diammonium hydrogen phosphate.

5. The method for preparing an anti-reflective polymer film for a perovskite cell having a lead ion sealing function according to claim 1, characterized in that: The transparent plasticizer is glycerol.

6. The method for preparing an anti-reflective polymer film for a perovskite cell having a lead ion sealing function according to any one of claims 1 to 5, characterized in that: The light absorption wavelength of the lead-based perovskite solar cell is less than the size of the micro-nano structure and is less than or equal to 10 microns.

7. The method for preparing an anti-reflection polymer film for a perovskite cell having a lead ion sealing function according to claim 6, characterized in that: The micro-nano structure is a pyramid structure.

8. An anti-reflection polymer film for perovskite cells with lead ion sealing function, characterized in that: It is prepared by the method according to any one of claims 1 to 7.

9. The anti-reflection polymer film for perovskite cells with lead ion sealing function as claimed in claim 8, characterized in that: The thickness of the polymer film is 150 to 200 microns.

10. An application of the anti-reflection polymer film for perovskite cells with lead ion sealing function as claimed in claim 8 or 9, characterized in that: The film is attached to the light-receiving surface of the lead-based perovskite solar cell.

Citation Information

Patent Citations

  • Biodegradable lead-fixing packaging coating applied to perovskite solar cell and preparation and packaging method of biodegradable lead-fixing packaging coating

    CN115073975A

  • Solar cell module and electric device

    WO2024082118A1

Cited By

  • Efficient and stable perovskite solar cell based on internal packaging strategy and preparation method and application of efficient and stable perovskite solar cell

    CN120091698A